A new PD-1-specific nanobody enhances the antitumor activity of T-cells in synergy with dendritic cell vaccine. (1st December 2021) - Shi, Wei; Yang, Xiaomei; Xie, Shenxia; Zhong, Dani; Lin, Xuandong; Ding, Ziqiang; Duan, Siliang; Mo, Fengzhen; Liu, Aiqun; Yin, Shihua; Jiang, Xiaobing; Xu, Zhi Ping (Gordon); et al.
Abstract: Despite the many successes and opportunities presented by PD-1 blockade in cancer therapies, anti-PD-1 monoclonal antibodies still face multiple challenges. Herein we report a strategy based on a nanobody (Nb) to circumvent these obstacles. A new PD-1-blocking Nb (PD-1 Nb20) in combination with tumor-specific dendritic cell (DC)/tumor-fusion cell (FC) vaccine that aims to improve the activation, proliferation, cytokine secretion, and tumor cell cytotoxicity of CD8 + T-cells. This combination was found to effectively enhance the in vitro cytotoxicity of CD8 + T-cells to kill human non-small cell lung cancer (NSCLC) HCC827 cells, hepatocellular carcinoma (HCC) HepG2 cells, and tongue squamous cell carcinoma (TSCC) Tca8113 cells. Moreover, CD8 + T-cells pre-treated with PD-1 Nb20 and tumor-specific DC/tumor-FCs significantly suppressed the growth of NSCLC-, HCC- and TSCC-derived xenograft tumors and prolonged the survival of tumor-bearing mice, through promoting T-cell infiltration to kill tumor cells and inhibiting tumor angiogenesis. These data demonstrate that PD-1 Nb20 in synergy with DC/tumor-FC vaccine augment the broad spectrum of antitumor activity of CD8 + T-cells, providing an alternative and promising immunotherapeutic strategy for tumor patients who are T-cell-dysfunctional or not sensitive to anti-PD-1 therapy. Graphical abstract: Image 1 Highlights: PD-1 Nb20 screened out from the well-established anti-PD-1 nanobody library has good biological activity, high PD-1 binding rate and specificity. PD-1 Nb20 specifically binds PD-1 epitopes on T-cells and liberates T-cell activity from negative effects of PD-1/PD-L1 pathway. The specific blocking of PD-1 by PD-1 Nb20 effectively improves the induction efficiency of tumor-reactive CD8 + T cells induced by DC/tumor-fusion cell (FC) vaccine. PD-1 Nb20 in synergy with DC/tumor-FC vaccine improves antitumor activity of T-cells against multiple tumor types.